Levamisole and Chinese medicinal herbs can modulate the serum interleukin-6 level in patients with recurrent aphthous ulcerations - Sun, Andy; Chia, Jean-San; Chang, Yu-Fong; Chiang, Chun-Pin (Journal of oral pathology & medicine, 2003)
Background:  Recurrent aphthous ulcerations (RAU) are common oral inflammatory lesions. Interleukin‐6 (IL‐6) is a pro‐inflammatory cytokine that has effects on cellular and humoral immunities. Previous studies have shown that the high serum IL‐6 levels in some RAU patients can be reduced by drug treatment. This finding suggests that IL‐6 may be a useful marker in evaluating therapeutic effects of RAU. Methods:  In this study, we used a solid phase, two‐site sequential chemiluminescent immunometric assay to determine the baseline serum levels of IL‐6 in a group of 228 patients with RAU, erythema multiforme (EM), traumatic ulcers (TU), oral submucous fibrosis (OSF), pemphigus vulgaris (PV), or Sjögren's syndrome (SS), and in 77 normal control subjects. Some RAU patients were treated with levamisole plus Chinese medicinal herbs or levamisole only for 0.5–5 months and their serum IL‐6 levels were measured after treatment. Results:  We found that about 99% of the normal control subjects and the patients with EM, TU, or OSF had a serum IL‐6 level within the normal limit of 5.0 pg/ml. However, 24% (48/197) RAU patients, 14% (1/7) EM patients, 43% (3/7) PV patients, and 100% (6/6) SS patients had a serum level of IL‐6 greater than 5.0 pg/ml. The mean serum level of IL‐6 in patients with RAU (3.6 ± 3.5 pg/ml, P < 0.001), minor type RAU (2.7 ± 2.0 pg/ml, P < 0.05), major type RAU (5.2 ± 4.6 pg/ml, P < 0.001), or herpetiform type RAU (4.1 ± 3.8 pg/ml, P < 0.01) was higher than that in normal control subjects. The mean serum level of IL‐6 in major type (P < 0.001) or in herpetiform type RAU patients (P < 0.05) was higher than that in minor type RAU patients. The mean reduction of serum IL‐6 level (10.0 ± 7.1 pg/ml) in RAU patients after treatment with levamisole plus Chinese medicinal herbs was significantly higher than that (5.1 ± 3.7 pg/ml) in RAU patients after treatment with levamisole only (P < 0.005), suggesting that the combination therapy is superior to the single therapy of levamisole only. Conclusion:  We conclude that levamisole and levamisole plus Chinese medicinal herbs can modulate the serum IL‐6 level in RAU patients. Although the therapeutic effect of RAU can be assessed by a decrease in the frequency, duration and number of the oral ulcerations, it can also be monitored by a reduction of serum IL‐6 level in RAU patients.